2014
DOI: 10.1111/phpp.12098
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of three phototherapy methods for the treatment of acne vulgaris in Chinese patients

Abstract: Phototherapy is efficacious for moderate to severe facial acne vulgaris.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 39 publications
1
33
0
1
Order By: Relevance
“…Interestingly, a high proportion of patients with severe acne (baseline IGA 4) benefited from this treatment. Study treatment was safe and very well tolerated, as previously reported, for blue light therapy …”
Section: Discussionsupporting
confidence: 73%
“…Interestingly, a high proportion of patients with severe acne (baseline IGA 4) benefited from this treatment. Study treatment was safe and very well tolerated, as previously reported, for blue light therapy …”
Section: Discussionsupporting
confidence: 73%
“…Compliance was excellent despite the young age of the patients and the long study period (at least 24 weeks considering the total duration of the Main and the Extension trials). Serious adverse events after treatment were not observed and as previously reported the BioPhotonic System was safe and well tolerated . One limitation of this trial might be that most the patients included were female (71%).…”
Section: Discussionmentioning
confidence: 77%
“…LPDL, which uses a wavelength of 595 nm, was more effective at decreasing ILC in patients with mild to severe acne when combined with PDT (67% vs. 100%) [70, 71]. Treatment with red (620–660 nm) and blue (400–500 nm) light are both moderately effective at decreasing ILC (up to 66% and up to 77%, respectively), and these efficacies can be enhanced when combined with PDT [58, 64, 67, 7282]. Red light PDT appears to be more effective when the photosensitizer is incubated under occlusion compared to no occlusion (59.4% and 31.7% ILC reduction, respectively) [80].…”
Section: Resultsmentioning
confidence: 99%
“…Red light PDT appears to be more effective when the photosensitizer is incubated under occlusion compared to no occlusion (59.4% and 31.7% ILC reduction, respectively) [80]. Blue-red (400–500 plus 620–660 nm) light therapy may be superior to either blue or red light alone, with ILC reductions of up to 90% reported [58, 8385]. …”
Section: Resultsmentioning
confidence: 99%